The impact of global and local cohesion on innovation in the pharmaceutical industry - Guler, Isin; Nerkar, Atul (Strategic Management Journal, 2012)
Abstract In this paper, we examine how the configuration of intraorganizational networks, and in particular, cohesion among members of an organization, influences organizations' innovative output. We argue that the cohesion among R&D scientists could be at a local level or a global level, and that local and global cohesion may have different impacts on firms' innovation performance. We test our hypotheses by examining the structure of the R&D collaboration networks within firms that operated in the pharmaceutical industry between 1981 and 1989, and their innovative outcomes—patents that led to new product launches. We find that local cohesion has a positive impact on the innovative performance of a firm, and global cohesion has a negative impact. Copyright © 2011 John Wiley & Sons, Ltd.